FAKTOR-FAKTOR YANG MEMPENGARUHI INVOLUSI UTERUS (STUDI KASUS DI BPM IDAROYANI DAN BPM SRI PILIH RETNO TAHUN 2014) - Ferdina Fitriana Mayasari; Wulandari Meikawati (Universitas Muhammadiyah Semarang, 2015)
Background:The maternal mortality rate because bleeding post partum have the highest rankwhere one causes postpartum hemorrhage is uteri atonia. If the uterus on the post partum failing in involution will cause something called subinvolusio often caused by infection and remain of the placenta in the uterus so that the uterus involution not gone normal or obstructed. If subinvolusio cannot will cause bleeding who continues or post partum haemorrhage until death. Methods: This type of analytical research with cross sectional approach. 32 The study population sample of mothers post partum and post partum mothers 30 studies with purposive random sampling technique. Analysis of these data using the Chi-square test with ? value of 0.05. Independent variable is the early mobilization, nutritional status, age, parity, while uteri involution is the dependent variable. Results: The results showed the majority (53.3%) of respondence aged <20 and > 35 years. Respondence who did early mobilization of (63.3%). Nutritional status of the respondence (76.7%) including normal nutritional status / LILA not KEK. The majority (66.7%) of respondence primi and multipara. There is a correlation between early mobilization, age, parity with uteri involution (p-value 0.023, p-value 0.000, p-value 0.000). There is no correlation between the nutritional status of uterus involution (p-value 0.666). Conclusion: postpartum hemorrhage caused by infection and remain of the placenta, this will lead to uterus involution process is hampered.